Molecular definitions of cell death subroutines: recommendations of the Nomenclature Committee on Cell Death 2012. - Galluzzi, L; Vitale, I; Abrams, J; Alnemri, E; Baehrecke, E; Blagosklonny, M; Dawson, T; Dawson, V; El-Deiry, W; Fulda, S; Gottlieb, E; Green, DR; et al. (2012)
In 2009, the Nomenclature Committee on Cell Death (NCCD) proposed a set of recommendations for the definition of distinct cell death morphologies and for the appropriate use of cell death-related terminology, including 'apoptosis', 'necrosis' and 'mitotic catastrophe'. In view of the substantial progress in the biochemical and genetic exploration of cell death, time has come to switch from morphological to molecular definitions of cell death modalities. Here we propose a functional classification of cell death subroutines that applies to both in vitro and in vivo settings and includes extrinsic apoptosis, caspase-dependent or -independent intrinsic apoptosis, regulated necrosis, autophagic cell death and mitotic catastrophe. Moreover, we discuss the utility of expressions indicating additional cell death modalities. On the basis of the new, revised NCCD classification, cell death subroutines are defined by a series of precise, measurable biochemical features.